Catalytic cracking catalyst containing alkaline metal and rare earth as well as preparation method and application of catalytic cracking catalyst

By introducing alkaline metals and rare earths in catalytic cracking catalysts, and using a combination of silicone -phosphate composite adhesive and forming fractive lobe molecular sieve, the problem of high hydrogen transfer activity in catalytic cracking reactions and the low production rate of hybridne production. Efficient low -carbon olefin production.

CN119368228APending Publication Date: 2025-01-28SHANDONG UNIV OF TECH

Patent Information

Application Number
CN202411962776.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the catalytic cracking reaction, the existing catalytic cracking catalysts have problems such as high hydrogen transfer activity, high alkane yield and low diene yield in catalytic cracking reactions, and the efficacy of the binder is difficult to fully exert.

Method used

The combination of alkaline metals and rare earth catalytic catalysts, combination of phosphate composite adhesives and forming fracture molecular sieves to reduce hydrogen transfer activity and improve the pore volume and response performance of the catalyst.

Benefits of technology

The production rate of alkanes such as methane and ethylene is significantly reduced, the bipyne (ethylene and acryl) revenue is increased, and the anti -abrasion strength and reaction performance of the catalyst are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a catalytic cracking catalyst containing alkaline metal and rare earth as well as a preparation method and application of the catalytic cracking catalyst, and belongs to the technical field of catalysts. The catalytic cracking catalyst containing the alkaline metal and the rare earth comprises 5-35% of a phosphorus-silicon composite binder, 10-60% of a shape-selective cracking molecular sieve, 0-25% of other molecular sieves, 0.01-5% of an alkaline metal compound in terms of oxide, 0.2-5% of a rare earth compound in terms of oxide, 0-15% of activated aluminum oxide and the balance of natural clay, wherein the total percentage is 100%. The phosphorus-silicon composite binder is prepared from the following components in percentage by weight: 15 to 55 percent of P2O5, 10 to 45 percent of SiO2 and 0.1 to 3 percent of RE2O3. The prepared catalytic cracking catalyst containing the alkaline metal and the rare earth not only improves the catalytic cracking activity of light hydrocarbon, but also is suitable for cracking of naphtha and mixed C4 raw materials, and can obviously reduce the hydrogen transfer activity in the reaction process, so that the yield of alkane such as methane and ethane is reduced, and the yield of diene is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalytic cracking catalyst containing alkaline metals and rare earths, and a preparation method and application thereof. Background Art

[0002] With the rapid development of the petrochemical industry, the demand for ethylene and propylene is growing. Naphtha steam cracking provides 90% of ethylene and 30% of propylene in my country. Although the steam cracking process is mature, it has disadvantages such as high construction cost, high energy consumption of the device (reaction temperature greater than 800℃), and large carbon emissions. In order to cope with the increasingly severe global energy consumption and environmental pollution problems, hydrocarbon catalytic cracking process technology using microsphere catalysts has been developed. This process converts long-chain hydrocarbons into high-value-added low-carbon olefins such as ethylene and propylene at a higher reaction temperature (600℃-700℃). In microsphere catalytic cracking catalysts, small and medium pore size shape-selective cracking molecular sieves and auxiliary metal elements are generally used as the main cracking components to achieve the purpose of increasing the production of propylene and ethylene by coordinating positive carbon ions and free radical reactions. Since the pores of small and medium pore size molecular sieves are easily blocked, the pore smoothness of the catalyst has an important influence on the production of low-carbon olefins. The existing catalyst preparation technology limits the yield of low-carbon olefins to a certain extent.

[0003] CN101249455A discloses an alkane lattice oxygen selective oxidation activation catalytic cracking catalyst, comprising 5-20% of lattice oxygen oxidation active oxide, 10-35% of cracking active component, 10%-40% of Al2O3, 25%-35% of kaolin, and the catalyst performs oxidation cracking reaction on alkanes in naphtha to convert them into ethylene and propylene. CN111822043A discloses a catalytic cracking catalyst for high ethylene production, comprising 10-65% of natural minerals, 6-60% of boron aluminum composite oxide, 22-75% of Y molecular sieve and shape-selective molecular sieve, 3-40% of inorganic oxide binder, and is used for cracking of cycloalkanes and cycloalkanes, and has a high ethylene yield. CN112138710A discloses a catalytic cracking catalyst, comprising 1-25% Y-type molecular sieve, 5-50% mesoporous MFI structure molecular sieve, 1-60% inorganic binder and 0-60% second clay, which has high ethylene selectivity in the catalytic cracking reaction of petroleum hydrocarbons. CN112138712A discloses a catalytic cracking catalyst, comprising 1-30% Y-type molecular sieve, 5-55% mesoporous phosphorus and metal-containing MFI structure molecular sieve, 1-60% inorganic binder and 0-60% second clay, which has better ethylene selectivity in the catalytic cracking reaction of petroleum hydrocarbons and produces more propylene and BTX. CN101035619A discloses a porous solid acid catalyst for producing light olefins, containing 42-60% HZSM-5 with a Si / Al molar ratio of 15-300, 12-38% layered compounds, 1-20% Al2O3, 1-4% P2O5, 10-15% SiO2 and 0.5-2.5% B2O3, and a mixture containing aluminum compounds and phosphorus compounds as a pillar-bonding aqueous solution, showing good catalytic activity. CN101939095A discloses a molecular sieve catalyst, including 0.01-5% MnO2, 1-15% P2O5, and an inorganic oxide precursor including Al2O3, SiO2 or Al2O3-SiO2 in the form of sol, gel or solution, and preparing light olefins by catalytic cracking of naphtha in a harsh environment of high temperature and high humidity. CN113509925A discloses a solid base catalyst, comprising 0.02-70% active component, 0.02-5% auxiliary agent, 2-20% molding auxiliary agent, and 20-95% solid base catalyst carrier. In the catalytic cracking process of heavy oil and residual oil with a residual carbon content greater than 10%, the coke yield of the catalyst is less than 10%, and the selectivity of low-carbon olefins in liquefied gas is greater than 80%. CN113769727A discloses a high-stability base catalyst, comprising 20-90% solid base catalyst carrier, 0.05-75% active component and 5-40% binder, which is used for heavy oil catalytic cracking reaction and significantly reduces the coke yield.CN113509925A discloses a solid base catalyst, comprising 0.02-70% active component, 0.02-5% auxiliary agent (transition metal), 2-20% molding auxiliary agent (binder), and 20-95% solid base catalyst carrier. In the catalytic cracking process of heavy oil and residual oil with a residual carbon content greater than 10%, the coke yield is less than 10%, and the selectivity of low-carbon olefins in liquefied gas is greater than 80%. CN 104888842A discloses a catalytic cracking catalyst, which is composed of 10-70wt% active component, 5-80wt% carrier, and 1-30wt% modified binder. It is suitable for the catalytic cracking reaction of C4 olefins to propylene, but it is difficult to give full play to the effect of the binder, and the wear resistance needs to be further improved. CN 115805098A discloses a catalytic cracking catalyst containing a phosphorus-silicon composite binder, which is composed of 5-35% phosphorus-silicon composite binder, 25-50% first molecular sieve, 0-25% second molecular sieve, 0.2-10% metal oxide, 0-15% activated alumina and the remainder clay. The phosphorus-silicon composite binder is obtained by mixing phosphoric acid and silica sol and aging at 30-95°C, which solves the problem of poor catalytic cracking catalyst effect to a certain extent. CN 117839754A discloses a catalytic cracking catalyst rich in transition metal clay and a preparation method thereof, including natural clay containing transition metals, phosphorus-silicon composite binder, shape-selective cracking molecular sieve, metal oxide and activated alumina and conventional clay. The invention uses natural clay containing transition metals and conventional clay in combination, and combines with a phosphorus-silicon composite binder to make the catalyst have a higher pore volume, giving full play to the cracking reaction performance of small and medium pore molecular sieves. The natural clay rich in transition metal elements contains more than 0.5% of transition metal elements, which can effectively increase the yield of low-carbon olefins such as ethylene and propylene in the catalytic cracking of naphtha.

[0004] The existing catalytic cracking catalyst mainly uses aluminum sol or phosphorus aluminum inorganic binder as the main binder to ensure the wear resistance of the microsphere catalytic cracking catalyst. Due to the small particle size of aluminum sol, it can block the pores of the catalyst to a large extent, limiting the effect of small and medium pore molecular sieves in increasing the production of light olefins; patents (such as CN 117839754A, CN 115805098A) disclose methods for preparing binders using modified silica sols such as phosphoric acid, but this method is difficult to fully exert the effect of the binder and does not show cracking reaction performance for carbon tetraalkanes. At the same time, the existing metal modified molecular sieve method cannot effectively reduce the hydrogen transfer activity, resulting in high hydrogen content and alkane yield, and reducing the yield of dienes (ethylene and propylene). Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a catalytic cracking catalyst containing alkaline metals and rare earth elements, and a preparation method and application thereof. In the catalytic cracking reaction of hydrocarbons (C4-C12), the simultaneous introduction of alkaline metals and rare earth elements can significantly reduce the hydrogen transfer activity, thereby reducing the yield of alkanes such as methane and ethane, and effectively improving the yield of dienes.

[0006] The present invention is achieved through the following technical solutions: A catalytic cracking catalyst containing alkaline metals and rare earths, comprising the following raw materials in percentage by weight: 5-35% phosphorus silicon composite binder, 10-60% shape selective cracking molecular sieve, 0-25% other molecular sieves, 0.01-5% alkaline metal compounds calculated as oxides, 0.2-5% rare earth compounds calculated as oxides, 0-15% activated alumina and the balance natural clay, totaling 100%; The phosphorus-silicon composite binder comprises the following raw materials in percentage by weight: 15-55% P2O5, 10-45% SiO2, 0.1-3% RE2O3, and a solid content of 25-65%.

[0007] Further, the phosphorus-silicon composite binder comprises the following raw materials in percentage by weight: 6-30% phosphorus-silicon composite binder, 15-55% shape-selective cracking molecular sieve, 0-20% other molecular sieves, 0.1-4% alkaline metal compounds in the form of oxides, 0.3-4.5% rare earth compounds in the form of oxides, 0-12% activated alumina and the balance natural clay, totaling 100%; The phosphorus-silicon composite binder comprises the following raw materials in percentage by weight: 18-50% P2O5, 12-42% SiO2, 0.2-2.5% RE2O3, particle size 6nm-30nm, pH 0.6-3.5.

[0008] Furthermore, the shape-selective cracking molecular sieve is one or more of ZSM-5, M-ZSM-5, IM-5, SAPO-34, SAPO-18, EU-1, ITQ-13, β zeolite, and MCM-22; the other molecular sieves are one or more of HY, USY, RE-USY, P-USY, and PRE-USY; the alkaline metal compound is one of calcium oxide, magnesium oxide, barium oxide, calcium carbonate, magnesium carbonate, magnesium nitrate, calcium nitrate, and barium nitrate in terms of oxide; the rare earth compound is one or more of Sc, Y, Ce, La, Pr, and Sm compounds; the activated alumina is derived from one or more of pseudo-boehmite, alumina monohydrate, alumina trihydrate, and amorphous alumina; the natural clay is one or more of kaolin, halloysite, montmorillonite, cross-linked layered clay, sepiolite, bentonite, hydrotalcite, diatomaceous earth, and rectorite.

[0009] Furthermore, the silicon-aluminum molar ratio of ZSM-5 is 15-150, and M-ZSM-5 is one or more of Fe-ZSM-5, Co-ZSM-5, Ni-ZSM-5, Mn-ZSM-5, Ce-ZSM-5, P-ZSM-5, and Fe-P-ZSM-5.

[0010] The present invention also discloses a method for preparing the above-mentioned catalytic cracking catalyst containing alkaline metals and rare earths, comprising the following steps: (1) Preparation of phosphorus-silicon composite binder: phosphoric acid, silica sol and rare earth compound are mixed, and aged at 30°C-95°C for 0.1-5h to obtain phosphorus-silicon composite binder; (2) Preparation of a catalytic cracking catalyst containing alkaline metals and rare earths: The phosphorus silicon composite binder prepared in step (1), shape selective cracking molecular sieve, other molecular sieves, alkaline metal compounds, rare earth compounds, activated alumina, natural clay and water are mixed to form a slurry with a solid content of 20%-60%, which is then spray dried and calcined to form a microsphere catalytic cracking catalyst.

[0011] Furthermore, the phosphoric acid in step (1) is orthophosphoric acid or phosphorous acid; the phosphoric acid concentration is 20-62% in terms of P2O5 content; the silica sol concentration is 15-50% in terms of SiO2 content, the pH value is 1.0-7.0, the sodium oxide content is 20-200 ppm, and the particle size is 4-35 nm; and the rare earth compound is one or more of Sc, Y, Ce, La, Pr, and Sm oxides.

[0012] Furthermore, the spray drying conditions in step (2) are an inlet temperature of 300-600°C, an exhaust gas temperature of 80-300°C, and the calcination conditions are 300-650°C, 0.3-3.0h.

[0013] Furthermore, the spray drying conditions in step (2) are an inlet temperature of 350-580°C, an exhaust gas temperature of 100-250°C, and a roasting condition of 350-600°C for 0.5-2.0h.

[0014] In the present invention, the catalytic cracking catalyst containing alkaline metal and rare earth is used in the catalytic cracking reaction of light hydrocarbons, and the light hydrocarbons are petroleum naphtha or C4 alkanes.

[0015] Furthermore, the conditions for the catalytic cracking are: temperature 400-750°C, time 0.5-10s, catalyst-oil ratio 3-40.

[0016] Beneficial Effects The catalytic cracking catalyst containing alkaline metals and rare earth elements prepared by the present invention simultaneously introduces alkaline metals and rare earth elements, which not only improves the catalytic cracking activity of light hydrocarbons, but is also suitable for the cracking of naphtha and mixed C4 raw materials, and can also significantly reduce the hydrogen transfer activity in the reaction process, reduce the yield of alkanes such as methane and ethane, thereby effectively improving the diene yield. DETAILED DESCRIPTION

[0017] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0018] The present invention relates to an analytical testing method: (1) Kaolinite and halloysite: X-ray diffraction method; (2) Relative crystallinity and unit cell parameters: X-ray diffraction method; (3) Elemental composition and silicon-aluminum ratio: XRF fluorescence method; (4) Solid content: ignition method, 800℃ / 1 hour; (5) Average particle size: laser particle size analyzer method; (6) Particle size: TEM analysis; (7) Specific surface area and pore volume: nitrogen adsorption method; (8) Wear index: abrasion tester straight tube method; (9) Microreaction activity (MA): The feedstock oil is Dagang light diesel oil, the catalyst loading is 5.0 g, the catalyst-oil ratio is 3.2, the reaction temperature is 460°C, the reaction time is 70 seconds, MA = (gasoline below 200°C in the product + gas + coke) / total oil input × 100%.

[0019] Specifications of raw materials used in the present invention (all in weight percentage): (1) 1# orthophosphoric acid, P2O5 61.5%; 2# orthophosphoric acid, P2O5 30%; 1# silica sol, SiO2 30%, pH 2.8, sodium oxide 120ppm, particle size 12nm; 2# silica sol, SiO2 40%, pH 4.6, sodium oxide 150ppm, particle size 18nm; concentrated hydrochloric acid, 37%, all are industrial products; (2) Manganese dichloride, cobalt nitrate (Co(NO3)2.6H2O), aluminum nitrate (Al(NO3)3.9H2O), and boric acid (H3BO3) were all chemically pure.

[0020] (3) Calcium oxide, magnesium oxide, calcium carbonate, barium carbonate, magnesium nitrate, cerium oxide, lanthanum oxide, cerium nitrate, lanthanum nitrate, yttrium nitrate, lanthanum carbonate, lanthanum chloride and yttrium oxide, all of chemically pure quality; (4) 1# ZSM-5, silicon-aluminum ratio 50, relative crystallinity 93%, sodium oxide 0.07%, solid content 95.0%; 2# ZSM-5, silicon-aluminum ratio 70, relative crystallinity 89%, sodium oxide 0.10, solid content 94.5%; Fe-ZSM-5, Fe2O3 1.8%, solid content 92.0%; Mn-ZSM-5, MnO 2.1%, solid content 94.5%, all are industrial products; (5) USY, unit cell parameter 2.427nm, solid content 96.0%; RE-USY, RE2O31.9%, solid content 95.2%, β zeolite, silicon-aluminum ratio 26, solid content 94.4%; SAPO-34, relative crystallinity 88%, solid content 93.2%, all are industrial products; (6) Pseudo-boehmite, solid content 61.0%; alumina monohydrate, solid content 71.5%; aluminum sol, Al2O3 23.5%, all are industrial products; (7) Kaolin: kaolinite content 87%, solid content 87.5%, average particle size 3.9 μm; halloysite: halloysite content 76%, solid content 85.4%, average particle size 4.1 μm; montmorillonite: solid content 84.6%, average particle size 4.3 μm, all are industrial products.

[0021] Example 1 (1) Preparation of phosphorus-silicon composite binder: 900 g of 1# orthophosphoric acid, 50 g of lanthanum chloride and 1100 g of 1# silica sol were mixed evenly and reacted at 85°C for 0.2 hours to obtain 1# phosphorus-silicon composite binder. The main composition properties of 1# phosphorus-silicon composite binder are shown in Table 1; (2) Preparation of catalytic cracking catalyst containing alkaline metals and rare earths: The raw material ratios are shown in Table 2 below. Specifically, deionized water, kaolin, USY and 1# ZSM-5 were mixed and slurried for 80 minutes, magnesium nitrate and lanthanum carbonate (in terms of oxide) were added and stirred for 30 minutes, 1# phosphorus silicon binder was added and slurried for 40 minutes, and a slurry with a solid content of 50% was obtained after high-speed shear treatment. The slurry was then spray-dried (inlet temperature 540°C, exhaust gas temperature 170°C), and the obtained microspheres were calcined at 600°C for 40 minutes to obtain a catalytic cracking catalyst containing alkaline metals and rare earths (A-1).

[0022] Example 2 (1) Preparation of phosphorus-silicon composite binder: 1340 g of 1# orthophosphoric acid, 30 g of lanthanum chloride and 660 g of 1# silica sol were mixed evenly and reacted at 40°C for 2.0 hours to obtain 2# phosphorus-silicon composite binder. The main composition properties of 2# phosphorus-silicon composite binder are shown in Table 1; (2) Preparation of catalytic cracking catalyst containing alkaline metals and rare earths: The raw material ratios are shown in Table 2 below. Specifically, deionized water, halloysite, pseudo-boehmite, Fe-ZSM-5 and 2#ZSM-5 are mixed and slurried for 60 minutes, calcium nitrate and cerium oxide are added and stirred for 20 minutes, 2#phosphosilicate binder is added and slurried for 30 minutes, and subjected to high-speed shear treatment to obtain a slurry with a solid content of 40%, which is then spray-dried (inlet temperature 550°C, exhaust gas temperature 180°C), and the obtained microspheres are calcined at 550°C for 60 minutes to obtain a catalytic cracking catalyst containing alkaline metals and rare earths (A-2).

[0023] Example 3 (1) Preparation of phosphorus-silicon composite binder: 1320 g 2# orthophosphoric acid, 70 g cerium nitrate and 1000 g 2# silica sol were mixed evenly and reacted at 50°C for 0.5 hour to obtain 3# phosphorus-silicon composite binder. The main composition properties of 3# phosphorus-silicon composite binder are shown in Table 1. (2) Preparation of catalytic cracking catalyst containing alkaline metals and rare earths: The raw material ratios are shown in Table 2 below. Specifically, deionized water, montmorillonite, SAPO-34 and 2#ZSM-5 were mixed and slurried for 80 min, magnesium nitrate, calcium oxide and yttrium oxide were added and stirred for 30 min, 3#phosphorus silicon binder was added and slurried for 40 min, and subjected to high-speed shear treatment to obtain a slurry with a solid content of 45%, which was then spray-dried (inlet temperature 540°C, exhaust gas temperature 170°C). The obtained microspheres were calcined at 600°C for 40 min to obtain a catalytic cracking catalyst containing alkaline metals and rare earths (A-3).

[0024] Example 4 (1) Preparation of phosphorus silicon composite binder: Preparation of 3# phosphorus silicon binder Copper Example 3 Step (1); (2) Preparation of catalytic cracking catalyst containing alkaline metals and rare earths: The raw material ratios are shown in Table 2 below. Specifically, deionized water, kaolin, alumina monohydrate, REUSY and 2#ZSM-5 were mixed and slurried for 80 min, calcium carbonate and cerium nitrate were added and stirred for 30 min, 3#phosphorus silicon binder was added and slurried for 40 min, and a slurry with a solid content of 38% was obtained after high-speed shear treatment. The slurry was then spray-dried (inlet temperature 560°C, exhaust gas temperature 180°C), and the obtained microspheres were calcined at 600°C for 40 min to obtain a catalytic cracking catalyst containing alkaline metals and rare earths (A-4).

[0025] Example 5 (1) Preparation of phosphorus-silicon composite binder: 1340 g of 1# orthophosphoric acid, 30 g of yttrium nitrate and 660 g of 1# silica sol were mixed evenly and reacted at 70°C for 2.0 hours to obtain 4# phosphorus-silicon composite binder. The main composition properties of 4# phosphorus-silicon composite binder are shown in Table 1; (2) Preparation of catalytic cracking catalyst containing alkaline metals and rare earths: The raw material ratios are shown in Table 2 below. Specifically, deionized water, halloysite, pseudo-boehmite, Fe-ZSM-5 and 2#ZSM-5 were mixed and slurried for 60 min, calcium nitrate and cerium oxide were added and stirred for 20 min, 4#phosphosilicate binder was added and slurried for 30 min, and subjected to high-speed shear treatment to obtain a slurry with a solid content of 38%, which was then spray-dried (inlet temperature 550°C, exhaust gas temperature 180°C). The obtained microspheres were calcined at 550°C for 60 min to obtain a catalytic cracking catalyst containing alkaline metals and rare earths (A-5).

[0026] Comparative Example 1 (1) According to Example 1 of CN 117839754A, 900 g of orthophosphoric acid (1# orthophosphoric acid) and 1100 g of silica sol (1# silica sol) were mixed evenly and reacted at 80°C for 0.2 h to obtain a phosphorus-silicon composite binder; (2) Deionized water, kaolin and ZSM-5 (1#ZSM-5) were mixed and slurried for 60 minutes, and then manganese chloride was added and stirred for 20 minutes. Then the phosphorus silicon composite binder prepared in step (1) was added and slurried for 30 minutes. After high-speed shear treatment, a slurry with a solid content of 45% was obtained, which was then spray-dried and formed at an inlet temperature of 560°C and an exhaust gas temperature of 190°C. The spray microspheres were calcined at 550°C for 60 minutes to obtain a catalytic cracking catalyst (D-1) of Comparative Example 1. The specific raw material ratios are shown in Table 2.

[0027] Comparative Example 2 According to Example 5 of CN 115805098A, deionized water, kaolin and ZSM-5 were mixed and beaten for 60 minutes, and then MnO was added and stirred for 20 minutes. Then, 1# phosphorus silicon composite binder (the raw material ratios are shown in Table 1) was added and beaten for 30 minutes. After high-speed shear treatment, a slurry with a solid content of 45% was obtained, which was then spray-dried and formed (inlet temperature 550°C, tail gas temperature 140°C). The microspheres were calcined at 550°C for 60 minutes to obtain a comparative catalytic cracking catalyst (D-2). The specific raw material ratios are shown in Table 2.

[0028] Table 1 Composition of the phosphorus-silicon composite binder prepared in Examples 1 to 4 (wt%) ; Table 2 Raw material ratios and performances of catalytic cracking catalysts containing alkaline metals and rare earths prepared in Examples 1 to 4 .

[0029] Application Example 1 Catalytic cracking naphtha effect: The catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were treated at 800° C. and 100% water vapor for 10 hours respectively; in a fixed fluidized bed device, a catalytic cracking reaction was carried out using the naphtha shown in Table 3 as a raw material, the reaction temperature was 650° C., the catalyst-to-oil ratio was 15, and the catalyst loading was 60 g; the catalytic cracking products were analyzed, and the results are shown in Table 4. It can be seen from Table 4 that, compared with the comparative catalyst (Comparative Examples 1 to 2), the catalytic cracking catalyst containing alkaline metals and rare earths prepared by the present invention has a higher pore volume, fully exerts the reaction performance of the small and medium pore size shape-selective cracking molecular sieve, has a high liquefied gas yield and a diene (ethylene + propylene) yield, and a reduced alkane yield, showing a better catalytic cracking reaction performance.

[0030] Table 3 Naphtha composition ; Table 4 Catalytic cracking performance of petroleum naphtha .

[0031] Application Example 2 Catalytic cracking mixed C4 effect: The catalysts prepared in Example 1 and Comparative Examples 1-2 were treated at 800°C and 100% water vapor for 10 hours respectively; a catalytic cracking reaction was carried out on a fixed fluidized bed device using the mixed C4 shown in Table 5 as a raw material, the reaction temperature was 665°C, the catalyst-oil ratio was 20, and the catalyst loading was 60g; the catalytic cracking product was analyzed, and the results are shown in Table 6. As can be seen from Table 6, compared with the comparative catalyst (Comparative Examples 1-2), the catalytic cracking catalyst containing alkaline metals and rare earths prepared by the present invention using mixed C4 as a reaction raw material has a high diene (ethylene + propylene) yield and a low methane yield, showing a better catalytic cracking reaction performance.

[0032] Table 5 Composition of mixed carbon four ; Table 6 Catalytic cracking performance of naphtha .

Claims

1. A catalytic cracking catalyst containing an alkaline metal and a rare earth, characterized in that: The raw materials include the following weight percentages: 5-35% phosphorus silicon composite binder, 10-60% shape selective cracking molecular sieve, 0-25% other molecular sieves, 0.01-5% basic metal compounds calculated as oxides, 0.2-5% rare earth compounds calculated as oxides, 0-15% activated alumina and the balance natural clay, totaling 100%; The phosphorus-silicon composite binder comprises the following raw materials in percentage by weight: 15-55% P2O5, 10-45% SiO2, 0.1-3% RE2O3, and a solid content of 25-65%.

2. The catalytic cracking catalyst containing alkaline metals and rare earths according to claim 1, characterized in that: The raw materials include the following weight percentages: 6-30% phosphorus silicon composite binder, 15-55% shape selective cracking molecular sieve, 0-20% other molecular sieves, 0.1-4% basic metal compounds in the form of oxides, 0.3-4.5% rare earth compounds in the form of oxides, 0-12% activated alumina and the balance natural clay, totaling 100%; The phosphorus-silicon composite binder comprises the following raw materials in percentage by weight: 18-50% P2O5, 12-42% SiO2, 0.2-2.5% RE2O3, particle size 6nm-30nm, pH 0.6-3.

5.

3. The catalytic cracking catalyst containing alkaline metals and rare earths according to claim 1, characterized in that: The shape-selective cracking molecular sieve is one or more of ZSM-5, M-ZSM-5, IM-5, SAPO-34, SAPO-18, EU-1, ITQ-13, β zeolite, and MCM-22; the other molecular sieves are one or more of HY, USY, RE-USY, P-USY, and PRE-USY; the alkaline metal compound is one of calcium oxide, magnesium oxide, barium oxide, calcium carbonate, magnesium carbonate, magnesium nitrate, calcium nitrate, and barium nitrate in terms of oxide; the rare earth compound is one or more of Sc, Y, Ce, La, Pr, and Sm compounds; the activated alumina is derived from one or more of pseudo-boehmite, alumina monohydrate, alumina trihydrate, and amorphous alumina; the natural clay is one or more of kaolin, halloysite, montmorillonite, cross-linked layered clay, sepiolite, bentonite, hydrotalcite, diatomaceous earth, and rectorite.

4. The catalytic cracking catalyst containing alkaline metals and rare earths according to claim 3, characterized in that: The silicon-aluminum molar ratio of ZSM-5 is 15-150, and M-ZSM-5 is one or more of Fe-ZSM-5, Co-ZSM-5, Ni-ZSM-5, Mn-ZSM-5, Ce-ZSM-5, P-ZSM-5, and Fe-P-ZSM-5.

5. A method for preparing a catalytic cracking catalyst containing an alkaline metal and a rare earth as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of phosphorus-silicon composite binder: phosphoric acid, silica sol and rare earth compound are mixed, and aged at 30°C-95°C for 0.1-5h to obtain phosphorus-silicon composite binder; (2) Preparation of a catalytic cracking catalyst containing alkaline metals and rare earths: The phosphorus silicon composite binder prepared in step (1), shape selective cracking molecular sieve, other molecular sieves, alkaline metal compounds, rare earth compounds, activated alumina, natural clay and water are mixed to form a slurry with a solid content of 20%-60%, which is then spray dried and calcined to form a microsphere catalytic cracking catalyst.

6. The method for preparing a catalytic cracking catalyst containing alkaline metals and rare earths according to claim 5, characterized in that: The phosphoric acid in step (1) is orthophosphoric acid or phosphorous acid; the phosphoric acid concentration is 20-62% in terms of P2O5 content; the silica sol concentration is 15-50% in terms of SiO2 content, the pH value is 1.0-7.0, the sodium oxide content is 20-200 ppm, and the particle size is 4-35 nm; the rare earth compound is one or more of Sc, Y, Ce, La, Pr, and Sm oxides.

7. The method for preparing a catalytic cracking catalyst containing alkaline metals and rare earths according to claim 5, characterized in that: The spray drying conditions described in step (2) are an inlet temperature of 300-600°C and an exhaust gas temperature of 80-300°C, and the roasting conditions are 300-650°C and 0.3-3.0h.

8. The method for preparing a catalytic cracking catalyst containing alkaline metals and rare earths according to claim 7, characterized in that: The spray drying conditions in step (2) are an inlet temperature of 350-580°C and an exhaust gas temperature of 100-250°C, and the calcination conditions are 350-600°C and 0.5-2.0h.

9. Use of the catalytic cracking catalyst containing alkaline metal and rare earth according to any one of claims 1 to 4 in catalytic cracking of light hydrocarbons, characterized in that: The light hydrocarbons are naphtha or tetraalkane.

10. Use of the catalytic cracking catalyst containing alkaline metals and rare earths in catalytic cracking of light hydrocarbons according to claim 9, characterized in that: The conditions for the catalytic cracking are: temperature 400-750°C, time 0.5-10s, catalyst-oil ratio 3-40.

Citation Information

Patent Citations

  • Solid acid catalyst for producing light olefins and process using the same

    CN101035619A

  • Alkane crystal lattice oxygen selectivity oxidized activating catalyze cracking catalyst and method of use thereof

    CN101249455A

  • Catalyst for catalytic cracking of hydrocarbon, which is used in production of light olefin and production method thereof

    CN101939095A

  • Catalytic cracking catalyst, preparation method therefor and application thereof

    CN104888842A

  • Boron-containing catalytic cracking catalyst for increasing ethylene yield, preparation method and application method thereof

    CN111822043A

Cited By

  • Light hydrocarbon catalytic cracking catalyst for high-yield diene as well as preparation method and application of light hydrocarbon catalytic cracking catalyst

    CN120618523A